ISSUES OF PILGRIMAGE TOURISM DEVELOPMENT IN SAMARKAND OASIS (Scientific journal of the Fergana State University, 2023)
The article analyzes the development of pilgrimage tourism in the Samarkand oasis from a scientific and practical point of view. Analytical information about the holy places among the inhabitants of the oasis is presented after studying various legends and legends. Also, given the high importance of the religious factor in the social life of the population, the need for a wide development of pilgrimage tourism in places of worship has been proved.